A Challenging Management of Pseudomonas Perforated Corneal Ulcer with Multilayer Amniotic Membrane Transplantation and Pericardial Patch Graft in Pediatric Patient - Nabilah Afifah; Herwindo Dicky Putranto; Lely Retno Wulandari (Vision Science and Eye Health Journal, 2021)
Introduction: Pseudomonas aeruginosa (P. aeruginosa) is the leading cause of corneal ulcers in children 0 to 3 years of age compared to children in general. Case presentation: A two-months-old infant presented with whitish patches on the right eye two days before admission. A central corneal ulcer with a size of 7-mm x 7-mm accompanied by corneal thinning and melting was shown on the right cornea. It is was surrounded by greyish white creamy infiltrates. Corneal scraping showed Pseudomonas aeruginosa specimens. The cornea became perforate and crystalline lens extrusion was found at the day after intravenous ceftriaxone, levofloxacin eye drop, and cefazoline fortified eye drop administering. It might be caused by bacterial elastase and toxin which contributed to corneal damage. The patient was underwent a multilayer Amniotic Membrane Transplantation (AMT) combined with a pericardial patch graft due to corneal perforation. Two months post-AMT and pericardial patch graft the corneal perforation became entirely heal due to multilayer AMT, despite lysis of the pericardial patch graft. Corneal scar formation and reduction of vitreous opacity in ultrasound examination were shown. The patient was planned to undergo keratoplasty. Conclusions: Corneal ulcers due to Pseudomonas aeruginosa are highly destructive. The levels of infection, diagnostic, and therapeutic are still problems in pediatric patients. Lens extrusion and lysis of the pericardial patch graft are examples in this case. Keratoplasty is the definitive treatment for corneal ulcers with perforation; however, multilayer AMT combined with pericardial patch graft can be used as an alternative therapy to accelerate wound healing, reduce inflammation, and maintain the integrity of the eyeball.